2021
DOI: 10.1007/s40194-021-01095-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of competing notches on the fatigue strength of cut plate edges

Abstract: Material fatigue is one of the elementary causes of damage in steel construction besides corrosion and abrasion. Design recommendations require that weld seams are placed in less stressed areas due to the crack-sensitive nature of the welded areas. As a result, unwelded areas of the components such as free cut plate edges gain technical and economic relevance as locations for potential fatigue cracks. In the metal processing industry, different thermal cutting processes are frequently used. During the process,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Many studies showed that the width of HAZ is very narrow induced by thermal cutting processes [26,27].…”
Section: Sub-zones Of Heat-affected Zonementioning
confidence: 99%
“…Many studies showed that the width of HAZ is very narrow induced by thermal cutting processes [26,27].…”
Section: Sub-zones Of Heat-affected Zonementioning
confidence: 99%